الخصوصيات الثقافية في ظل إعلام العولمة بين ثقافة الأصالة وثقافة الحداثة - السعيد سليمان عواشرية (International Institute of Islamic Thought, 2015)
تبحث الورقة في التحدي الذي يمثلة إعلام العولمة للخصوصيات الثقاقية لبلدان العالم بصفة عامة والبلدان العربية والإسلامية بصفة خاصة، وتكشف عن أهم المشكلات التي يعاني منها الإعلام العربي في مواجهة ذلك التحدي. وتزداد حدة المشكلات حين لا يتوفر البديل الإعلامي المناسب، ويعاني ما تيسر منه فيها من معوقات عدة.كما اقترحت الورقة بعض الاستراتيجيات الكفيلة بمواجهة تحديات إعلام العولمة، وتقديم تصور للبديل الإعلامي الذي من شأنه تحقيق ذلك، موظفاً بعض سمات الحداثة في البناء المنشود، بصورة تربط ماضي الأمة بحاضرها من أجل المستقبل، وتؤسس على ثقافة الأصالة، في إطار الاحترام والاعتراف بالآخر. The paper examines the challenge posed by the globalization of the media to the cultural specificities of the countries of the world in general and the Arab and Islamic countries in particular. It reveals the problems of the Arab and Muslim media in facing that challenge.The problems become more acute when there is no appropriate media alternative, and with presence of the constraints that limit the function of what is available. The paper also suggests some strategies to meet the challenges of media globalization, an introduce and alternative media that employs some attributes of modernity, links the nation past with its present to build its future, and establish a culture of authenticity in a framework of respect and recognition of the other.